Effects of precipitating electrons in the ionosphere - Haschick, Aubrey D (Rhodes University, Faculty of Science, Department of Physics, 1974)
As early as 1896, around the time of the discovery of the electron by J.J. Thompson, Birkeland was led to propose that aurorae were caused by fast moving electrons or similarly charged particles emitted by the sun and 'sucked in towards' the auroral zones by the geomagnetic field. He later supported this idea by firing electrons at a dipole field surrounding a sphere covered with a fluorescent coating. Extensive ground based observations of auroral features eventually led, in 1950, to the initial direct evidence of the fact that auroral emissions are due to energetic charged particles, consisting partly of protons, entering the earth's atmosphere (Meinel, 1951). However, it was only in 1952 and 1953 that the first measurements of what was later interpreted as bremsstrahlung X- rays from precipitating electrons were made at auroral latitudes. (Meredith et aI, 1955) During the IGY, 1957 - 1958, a number of rockets were fired through and near, visible aurorae and large fluxes of low energy electrons were detected ... Intro., p. 1.
Keywords: Electrons; Electron precipitation; Ionosphere; Ionospheric electron density